Association between METS-IR and heart failure: a cross-sectional study - Su, Xiaozhou; Zhao, Chunli; Zhang, Xianwei (Frontiers in Endocrinology, 2024)
Background Prior research has indicated the importance of insulin resistance in the development of heart failure (HF). The metabolic score for insulin resistance (METS-IR), a novel measure for assessing insulin resistance, has been found to be associated with cardiovascular disease (CVD). Nevertheless, the relationship between METS-IR and heart failure remains uncertain.Methods This cross-sectional study collected data from the 2007-2018 National Health and Nutrition Examination Survey (NHANES). Multivariable logistic regression analysis and smoothing curve fitting were performed to explore the relationship between METS-IR and the risk of heart failure. Subgroup analysis and receiver operating characteristic (ROC) curve analysis were also conducted.Results A total of 14772 patients were included, of whom 485 (3.28%) had heart failure. We observed a significant positive association between METS-IR and the risk of heart failure in a fully adjusted model (per 1 unit increment in METS-IR: OR: 2.44; 95% CI: 1.38, 4.32). Subgroup analysis and interaction tests revealed no significant influence on this relationship. A saturation effect and nonlinear relationship between METS-IR and heart failure risk were found using a smoothed curve fitting analysis. The relationship was represented by an inverted J-shaped curve with an inflection point at 40.966.The results of our study indicated a J-shaped association between METS-IR and HF in adults in the United States. METS-IR may be a promising novel index for predicting the risk of heart failure. More longitudinal studies are needed to further verify causal relationships and validate the results in different classifications of heart failure populations.